DETERMINAN NILAI PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BEI - NABILA DWIEKALITA AZAHRA; SULISTYAWATI TOELLE (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
The research objective is to obtain empirical evidence regarding the influence of variables on firm value. The independent variables used are profitability, capital structure, company growth, liquidity, company size.The population used in this study are property and real estate sector companies listed on the Indonesia Stock Exchange for the period 2013-2023. The sampling technique used in this study was purposive sampling and there were 187 data that could be used as research samples. This study uses multiple regression analysis to analyze the data. The results of this study indicate that profitability and capital structure have a positive effect on firm value, while firm size has a negative effect on firm value. On the other hand, firm growth and liquidity have no influence on firm value.